Monitoramento, bioecologia e controle microbiano de helicoverpa armigera (hubner, 1805) (lepidoptera: noctuidae) no estado de Alagoas, Brasil - Silva, Letice Souza da (2017)
Considered an extremely polyphagous pest and with wide geographic distribution, the species Helicoverpa armigera (Hubner, 1805) (Lepidoptera: Noctuidae) was identified in Brazil in 2013 attacking soybean and cotton crops, compromising approximately 100% of production. Due to its devastating attack, the use of chemical insecticides was the alternative adopted by many producers in the country, being applied, most of the time in a disorderly way. Thus, the objective of this study was to evaluate the biology of the pest in natural (Abelmoschus esculentus L.) (Malvaceae) and artificial diet and its control with products based on bacterium Bacillus thuringiensis var. Kurstaki (DimyPel®) and viruses (Gemstar® - Virus VPN-HzSNPV) under laboratory conditions. For the monitoring, delta adhesive traps with sexual pheromone were used in 32 collection points, distributed in nine municipalities during the months of July 2013 to August 2014. Trap flooring was replaced every fortnight and sent to the Laboratory of Entomology of Federal University of Alagoas for identification and counting of adults. For the biological performance, the experimental design was completely randomized design with two treatments and 80 replicates. Newly hatched caterpillars were individualized and fed with natural and artificial diets, until stage of pupa. After 24 hours of their formation, pupae were weighed, sexed and conditioned in pairs in PVC cages for emergence of the adults. The variables evaluated were mortality (%), duration of larval and pupal stage (days), larval viability and pupa (%), sex ratio, fecundity (eggs/female) (daily and total), fertility (%), adult longevity (days), periods of pre-oviposition, oviposition and incubation (days). In relation to the life table, the net reproduction rate (Ro), average duration of one generation (T) (days), innate capacity to increase in number (rm) and finite ratio of increase (λ) were evaluated. For the control, the concentrations used were 0.0625; 0.125; 0.25; 0.5; 0.75; 1.0 mL and 0.03; 0.0625; 0.125; 0.25; 0.5; 0.75 mL, for bacteria and viruses, aiming to estimate the sublethal and lethal concentrations. After the adjustments, 50 2nd instar caterpillars were individualized and fed with cross sections of okra (A. esculentus L.) sprayed with the LC10, LC50 and LC99 (0.035, 0.154 and 2.18 mL and 0.017, 0.196 and 2.23 mL) of the products DimyPel® and Gemstar®, respectively. The variables evaluated were mortality (%), survival (days), duration of larval and pupal stages (days), larval and pupal viability (%), fecundity (eggs/female), fertility (%), adult longevity (days), sex ratio and period of oviposition (days). The experimental design was a completely randomized with seven treatments and 50 replications. The data obtained were analyzed by the statistical program SAS and means compared by Tukey’s test at 5% probability. The pest was predominant in the Agreste region of Alagoas, where 796 specimens were captured in the municipality of Arapiraca. The artificial diet interfered in the larval duration with 14.02 days, not influencing the other variables. The net reproduction rate and the finite rate of increase were 443.72 and 1.25 for the natural diet, and 445.20 and 1.24 for the artificial diet. The entomopathogenic agents shown to be effective in the mortality of larvae with 52% and 62% in LC50 for bacterium and viruses, respectively. For the other variables evaluated the product Gemstar® stood out in the LC50 by interfering on the biology of the pest. Based on the results obtained, the artificial and natural (A. esculentus L.) diets are appropriate for creation of H. armigera in laboratory. For the control, the product Gemstar® interferes in all stages of the biological cycle of the pest in the concentration of 0.196 mL.